Assessing the Nutritional Condition of The Elderly: Perspectives of Trained Health Workers and Significant Others in Countryside in Indonesia Inputs to an Action Plan - Fransisca Winandari (SOEPRA, 2020)
Background: Nutrition plays an important role in health maintenance, rehabilitation, and prevention and control of disease for the elderly. If undetected, nutritional problems among the elderly may result in more rapid deterioration of health and early death.  Methods: In this study, the researcher conducted descriptive correlational design to describe the perspectives of trained health workers and significant others on the nutritional condition of the elderly in terms of nutritional screening, nutritional assessment, and nutritional indication score. Results: The population of this study is the trained health workers in Bambanglipuro and the significant others of the elderly who met the inclusion criteria. There are 50 of trained health worker respondents and 112 significant other respondents. Their assessment was assessed by themselves and tested significant differences using the T-test. All the computed t values were less than T values of 1.96. This result shows that the null hypothesis is accepted, meaning there is no significant difference between the assessment of the trained health worker respondents and the significant other respondents on the nutritional condition of the elderly. It proved that the significant others completely knew about the nutritional condition of the elderly.Conclusions: Proposed action plan can be applied for enhancement of the nutritional condition of the elderly, such as to conduct a lecture related to the importance of assessing the physical problems of the patient, conduct a lecture related to the importance of assessing the patient’s mode feeding, conduct a training workshop related how to measure Calf Circumference and Mid-arm Circumference (MAC).